EFL Teachers’ Preparedness and Challenges in Supporting Young learners with reading comprehension disabilities :A Case Study on EFL Primary School Teachers in ELWiaam , Laghouat - BIGAA,Hadjer; KORICHI ,Sohila (Faculty of Letters and Foreign Languages Department of English, 2025)
Reading comprehension is considered fundamental in EFL classes; it shapes learners' understanding of diverse knowledge. Yet, in EFL classrooms, students often encounter challenges in developing this essential skill, commonly referred to as reading comprehension disabilities. These challenges, however, can be transformed into strengths when teachers are well-prepared to intervene using appropriate instructional strategies. By tailoring their methods to meet learners‘ needs, teachers can enhance reading comprehension abilities, leading to better learning outcomes and greater academic success. This study aims to explore teacher preparedness in applying effective evidence-based practices, including instructional strategies, multi-sensory and Scaffolding strategies, and phonics instruction, to enhance and support learners' reading comprehension skills. The study employed a mixed-methods approach, integrating both qualitative and quantitative techniques to obtain comprehensive and reliable insights. The data were collected through a questionnaire administered to 22 primary school EFL teachers in the Wiaam region of Laghouat, along with classroom observations carried out in a fifth-grade class comprising 28 pupils. These tools aimed to explore teachers‘ awareness and attitudes toward implementing instructional strategies to enhance reading comprehension skills. Out of 28 pupils, five were identified as struggling readers. The findings highlighted teachers‘ positive attitudes and perspectives regarding their formal training, which strengthened their preparedness to implement effective instructional strategies. Such readiness enabled them to better assist young EFL learners with reading comprehension difficulties and to provide practical solutions that address the main challenges hindering these learners‘ language development.